Sobat Ambyar: The Phenomenon of Fans, Social Media, and Modern Campursari Music in Popular Culture - Fathul Qorib; Sulih Indra Dewi (BBPSDMP KOMINFO MAKASSAR, 2021)
The popularity of the local Javanese music “Dangdut Campursari” increased dramatically from 2019 to 2020. Didi Kempot, who is nicknamed the God Father of Broken Heart, is a new phenomenon in Javanese music in the country. This research wants to see how the modern Campursari dangdut lovers “Sobat Ambyar” describe the identity of their community and see this phenomenon from the perspective of popular culture which includes trends, adaptability, and pop music consumerism. We documented Sobat Ambyar’s chat on social media, they managed and conducted in-depth interviews with the Instagram fanbase admin @sobatambyar. The results of this study indicated that Sobat Ambyar identifies themselves with the feelings, attitudes, and emotions of the songs sung by Didi Kempot. These identities tend to be sad and they are proud of that sadness. This Campursari has become a new commodity for industry and is popularized through the ways of modern culture which is simulated and marketed. Based on these findings, this study suggests that Sobat Ambyar remain authentic so that they can block mass culture that the younger generation is not aware of.Keyword : Fans, Instagram, Modern Campursari Music, Sobat Ambyar.